Opportunity spotting how to turn good ideas into business success - MacLennan, Nigel 1961-
This work tells you how to cultivate a creative state of mind and how to recognize the value of your own ideas. Whether its the search for new products and services or the need to adapt to rapidly changing markets, this book argues that ideas are the lifeblood of every organization.